La escultura como medio representativo de la carrera de artes plásticas utmach - Brito Vélez, Carlos Javier (2018)
The present project of titulación, aims to inform the student community the emergence of the "School of Fine Arts", name with which the current Career of Plastic Arts of the UTMACH was founded; for which sculpture is used as an ideal artistic medium, taking advantage of new materials and contemporary possibilities to achieve the dissemination and massification of that. Life and art through time have created a close communicative relationship, which strengthens history by marking an important value of sculpture, thanks to this plastic method can generate a contribution of knowledge, through the representation of a social event and cultural, full of merits and connotation of constant effort in order to conceive an objective, reaching the expectant in a diachronic manner. In search of altering space and time, this enriching contribution becomes a transcendental aesthetic contemplation in the academic community. As a main element of artistic promotion and diffusion, the Totem will be taken into account and what it represented for the ancestral culture that was to inform allegorically; then, in this aspect will be inserted compositional elements that are able to reach the viewer and thus demonstrate that the sculpture is of great importance because it transmits a message to the university spectator. By means of which the representation of this artistic object, named "perpetuidad memorial", was used as a way to recognize the effort and work of Soc. Ramiro Ordoñez, who saw in the city of Machala, the inherent need of implement a career that defines a cultural vision. For this, a small space is intervened within the UTMACH Campus Machala, which will be strategic, managing to convey the message directly about what art is and who formed it as an educational space for higher education. The arts degree is finally legitimized on September 2, 2003. Starting in 2004 its academic period, with the aim of training artists with extensive experience with a critical thinking that understands the importance of art in social development. Art seeks to confront the barriers that arise along the way, conjugating, signs and symbols, which put into question the present, retaking part of the past, to visualize the future, starting from images and pre-Columbian icons and those ideologies of contemplation by man guiding us in his anthropomorphic and sequential figures, capable of intervening in the educational and transitional space, orienting motivated students, predominating the will, delimited by curiosity. Art and public spaces, since a long time ago have been giving diversities of artistic interventions, giving another meaning to things. The totemic sculpture allows us to make visible, the artistic representation and other facts relevant to the construction of identity or origin, which will last over time, even if the work or the artist is extinguished, part of it will remain latent in the subconscious, as well as photographic records and electronic media.